1984
DOI: 10.1073/pnas.81.22.7248
|View full text |Cite
|
Sign up to set email alerts
|

Regional distribution of putative vasopressin receptors in rat brain and pituitary by quantitative autoradiography.

Abstract: Quantitative light microscopic autoradiography was used to map and characterize the distribution of [3H]AVP labeling at possible neuroregulatory sites was observed in the hippocampus, lateral septum, superficial cortex, cerebellum, nucleus tractus solitarious, adenohypophysis, and spinal cord.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
55
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(60 citation statements)
references
References 31 publications
5
55
0
Order By: Relevance
“…This effect, if present, seems to be restricted to penumbral tissue, because inhibition of AVP V 1 receptors does not affect CBF in the infarct core (Figure 1). Another explanation for AVP V 1 receptor-mediated neuroprotection might be that AVP V 1 receptors are widely expressed in the brain parenchyma (Brinton et al, 1984;Pearlmutter et al, 1988;Phillips et al, 1988;Young et al, 1999;Tribollet et al, 1999;Fernandez et al, 2001) where they have been implicated in intracellular calcium mobilization, activation of NMDA receptors, and superoxide anion generation (Urban and Killian, 1990;Hess et al, 1991;Gouzenes et al, 1999;Armstead, 2001), all conditions well known to be associated with neuronal cell death after cerebral ischemia (Lo et al, 2003). Accordingly, the positive effect AVP V 1 receptor inhibition on cell death might also be explained by a reduction of glutamate-and superoxide anion-mediated toxicity, as also discussed previously (Tanaka et al, 1994).…”
Section: Alternative Mechanisms Of Avp-mediated Brain Damagementioning
confidence: 99%
“…This effect, if present, seems to be restricted to penumbral tissue, because inhibition of AVP V 1 receptors does not affect CBF in the infarct core (Figure 1). Another explanation for AVP V 1 receptor-mediated neuroprotection might be that AVP V 1 receptors are widely expressed in the brain parenchyma (Brinton et al, 1984;Pearlmutter et al, 1988;Phillips et al, 1988;Young et al, 1999;Tribollet et al, 1999;Fernandez et al, 2001) where they have been implicated in intracellular calcium mobilization, activation of NMDA receptors, and superoxide anion generation (Urban and Killian, 1990;Hess et al, 1991;Gouzenes et al, 1999;Armstead, 2001), all conditions well known to be associated with neuronal cell death after cerebral ischemia (Lo et al, 2003). Accordingly, the positive effect AVP V 1 receptor inhibition on cell death might also be explained by a reduction of glutamate-and superoxide anion-mediated toxicity, as also discussed previously (Tanaka et al, 1994).…”
Section: Alternative Mechanisms Of Avp-mediated Brain Damagementioning
confidence: 99%
“…Nevertheless, in these regions, the presence of OT and VP receptors is subject to controversy. Indeed, using autoradiography, many authors have detected [3H]OT or ['HIVP labelling in the neural lobe (10,(18)(19)(20)(21)(22), but few of them have stated that this labelling was not displaced or only partly so by an excess of unlabelled hormone ( 1 I , 13). The complete disappearance of [3H]VP binding after stalk transection indicated that the binding sites were presynaptic (21).…”
mentioning
confidence: 99%
“…The absence, or very low levels, of [3H]VP or [3H]OT binding has been reported by some authors (21)(22)(23) in Brattleboro rats, while observations reported by Brinton et 01. (18) (20).…”
mentioning
confidence: 99%
“…Immuno-electron microscopic studies have shown that the AVP present in paraventricular neurones is contained within vesicle-like structures (Buijs & Swaab, 1979;Voorn & Buijs, 1983). Moreover, binding studies have revealed specific binding sites for AVP on neural membranes in the NTS (Dorsa et al, 1983;Brinton et al, 1984). This 'Author for correspondence.…”
Section: Introductionmentioning
confidence: 99%